A high cycle rate diaphragm and preparation method thereof
By using the coating technology that synergistically interacts with PMMA and alumina in the lithium-ion battery separator, the shortcomings in the existing separator in terms of safety performance and interface adhesion are solved, and the preparation of high-cycle magnification separator is achieved, which extends the cycle life of the battery and improves the mechanical properties of the separator.
Patent Information
- Application Number
- CN202211150890.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-21
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2042-09-21
AI Technical Summary
The existing lithium-ion battery separators have shortcomings in improving safety performance and interface adhesion, resulting in reduced battery cycle life and insufficient electrolyte reserves.
Using a coating technology that synergistically interacts with PMMA and alumina, a high-cycle magnification separator is prepared through specific stirring and ultrasonic treatment methods. The method includes blending the dispersant, pure water, alumina powder, isopropanol, CMC, PMMA and wetting agent, and forming a coating slurry by vacuum oscillation and stirring, followed by coating and drying on the PE film to form a high cycle rate separator.
It improves the coating adhesion and conductivity of the diaphragm, extends the cycle life of the battery, enhances the tensile and impact resistance of the diaphragm, reduces the heat shrinkage rate, and avoids the battery's thermal runaway.
Smart Images

Figure CN115483500B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery separators, and in particular relates to a high cycle rate separator and a preparation method thereof. Background Art
[0002] As environmental problems become increasingly severe, more and more new energy projects have received attention from the country and society, among which electric vehicles are particularly popular. As the power source of electric vehicles, the safety and endurance of lithium-ion batteries are the focus of scientific research. For modern people with a fast-paced life, the number of times lithium batteries are charged and used and the utilization rate of batteries are the focus of people's attention, and lithium battery separators play an important role.
[0003] The mainstream products on the market include PDVF (spraying), ceramic coating diaphragms and PVDF ceramic composite diaphragms. Among them, PVDF coating mainly provides interface adhesion and increases the hardness of the battery cell, while ceramic coating mainly provides good safety performance. A single PVDF or ceramic coating cannot provide these two functions at the same time. Although the composite coating can provide two functions at the same time, there are problems such as thick thickness and high air permeability. If the diaphragm is too permeable, pores will be blocked, reducing the shuttle of lithium ions and affecting the battery cycle life. In addition, the composite coating has a low liquid absorption capacity, resulting in insufficient electrolyte reserves in the battery system, causing an increase in interface resistance.
[0004] Based on the above, the present invention uses PMMA, commonly known as organic glass, to improve the coating adhesion of the diaphragm and the battery cycle rate. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention aims to provide a method for preparing a high cycle rate diaphragm.
[0006] Another object of the present invention is to provide a high cycle rate diaphragm obtained by the above preparation method.
[0007] The purpose of the present invention is achieved through the following technical solutions.
[0008] A method for preparing a high cycle rate diaphragm comprises the following steps:
[0009] Step 1, first stirring and blending a dispersant and pure water, then adding alumina powder and stirring and blending for a second time to obtain a mixed solution, and simultaneously performing ultrasound during the above-mentioned second stirring and blending process, adding isopropanol, CMC, PMMA and a wetting agent to the mixed solution after the second stirring, stirring and blending under vacuum oscillation, and preparing a coating slurry; wherein the mass fraction ratio of PMMA, alumina, pure water, wetting agent, dispersant, isopropanol and CMC is (5-18): (20-30): (51.5-70.9): (0.03-0.09): (0.1-0.2): (3-6): (2.5-7).
[0010] Step 2, coating the coating slurry obtained in step 1 on a PE film to obtain a coating film.
[0011] Step 3, drying the coating film obtained in step 2 to obtain a high cycle rate diaphragm.
[0012] In the above technical solution, in step 1, the dispersant is a silicate, which can evenly disperse inorganic particles that are difficult to dissolve in liquid, and can also prevent the sedimentation and aggregation of particles, thereby forming an amphiphilic agent required for a stable suspension.
[0013] In the above technical solution, in step 1, the wetting agent is sodium hexametaphosphate, which mainly functions to reduce surface tension and enhance slurry fluidity.
[0014] In the above technical solution, in step 1, the rotation speed of the stirring and blending is 2000-3100r / min, the revolution speed is 20-40r / min, and the stirring time is 5-45min.
[0015] In the above technical solution, in step 1, the rotation speed of the secondary stirring and blending is 2000-3100r / min, the revolution speed is 20-50r / min, and the stirring time is 10-30min.
[0016] In the above technical solution, in step 1, the ultrasound has an ultrasonic frequency of 20-50KHZ
[0017] In the above technical solution, in step 1, the vacuum oscillation stirring and blending has a rotation speed of 1000-3000 r / min, a revolution speed of 20-40 r / min, an ultrasonic oscillation frequency of 5-60 kHz, and a stirring time of 15-30 min.
[0018] In the above technical solution, preferably, in the step 1, the stirring and blending is carried out using a planetary stirring device.
[0019] In the above technical solution, in step 2, the coating is single-sided coating.
[0020] In the above technical solution, in step 2, the coating speed is 30-50 m / min.
[0021] In the above technical solution, in step 2, the coating thickness is 2-4 μm.
[0022] In the above technical solution, in step 3, the drying is performed by pulling the product into a drying device via a pulling roller for drying.
[0023] In the above technical solution, in step 3, the drying temperature is 50-70° C., and the drying time is 1-5 min.
[0024] Another aspect of the present invention also includes a high cycle rate diaphragm obtained by the above preparation method.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] 1. The aluminum oxide and PMMA on the surface of the high cycle rate diaphragm of the present invention synergistically play a role in improving the ionic conductivity of the diaphragm. Among them, the main component of PMMA is polymethyl methacrylate, which can effectively improve the cycle rate of the battery during the charge and discharge process, such as Figure 1 As shown, the spherical objects on the coating are PMMA, which will not affect the shuttling of ions in the battery. In addition, its particle size and particle size distribution are uniform, so that the high cycle rate diaphragm has enhanced tensile and impact resistance and strong resistance to deformation (good rigidity, good resistance to impact deformation, and its characteristics will not change with long-term use).
[0027] 2. The spatial stability and flatness of the high cycle rate diaphragm are also improved, and the thermal shrinkage rate is smaller, which greatly avoids the thermal runaway of the battery caused by short circuit due to thermal shrinkage. For the diaphragm using alumina and PVDF, a large number of nano-sphere glues completely block the gaps in the alumina coating. Figure 2 As shown, the shuttling ability of ions is weakened.
[0028] 3. In terms of thickness, both PMMA and PVDF act as adhesives, and PMMA is embedded between the alumina coatings, which increases the adhesion of the diaphragm coating and reduces the coating thickness; while PVDF+alumina is sprayed after the alumina coating is applied, and PVDF is bonded to the alumina coating, which also increases the coating thickness. Therefore, this arrangement of PMMA increases the adhesion of the diaphragm coating and reduces the coating thickness. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a scanning electron microscope image of the surface of the diaphragm obtained in Example 1, that is, a high cycle rate diaphragm using the synergistic effect of aluminum oxide and PMMA.
[0030] Figure 2 This is a scanning electron microscope image of the diaphragm obtained in Comparative Example 1, that is, the diaphragm surface under the synergistic effect of aluminum oxide and PVDF. DETAILED DESCRIPTION
[0031] Example 1
[0032] A method for preparing a high cycle rate diaphragm comprises the following steps:
[0033] Step 1, the required raw materials are 7 parts by mass of PMMA (35% solid content), 28 parts by mass of alumina, 55.8 parts by mass of pure water, 0.2 parts by mass of dispersant, 4 parts by mass of isopropanol, 3 parts by mass of CMC (5% solid content) and 0.04 parts by mass of wetting agent; the dispersant and pure water are stirred and blended in a planetary stirring device (with ultrasonic oscillation, vacuum, and high-speed dispersion functions) for 5 minutes at a time, the stirring rotation speed is 3100r / min, the revolution speed is 20r / min, and then the alumina powder is poured into the planetary stirring device (with ultrasonic oscillation, vacuum, and high-speed dispersion) The mixture was stirred and blended for 10 minutes in a planetary stirring device (with vacuum function), wherein the stirring speed of the device was 3100 r / min, and the revolution speed was 20 r / min; and ultrasound (frequency 50 kHz) was simultaneously performed during the above-mentioned secondary stirring and blending process; after the secondary stirring, isopropanol, CMC, PMMA and wetting agent were added to the mixed solution, and the planetary stirring device was turned on again (the vacuum function was turned on, the rotation speed of the device was adjusted to 1000 r / min, the revolution speed was 40 r / min, and the ultrasonic oscillation frequency was 5 kHz) for vacuum oscillation stirring and blending for 20 minutes to prepare a coating slurry.
[0034] Step 2, placing the PE film on a coating machine equipped with the coating slurry prepared in step 1 for single-side coating, controlling the coating speed to 30 m / min, and controlling the coating thickness after coating to 2 μm, to obtain a coating film;
[0035] Step 3, the coating film obtained in step 2 is pulled into a drying device through a traction roller for drying, the drying temperature is required to be 50° C., the drying time is 5 minutes, and a high cycle rate diaphragm is obtained.
[0036] Example 2
[0037] A method for preparing a high cycle rate diaphragm comprises the following steps:
[0038] Step 1, the required raw materials are 8 parts by mass of PMMA (35% solid content), 29 parts by mass of alumina, 55.8 parts by mass of pure water, 0.2 parts by mass of dispersant, 4 parts by mass of isopropanol, 2.95 parts by mass of CMC (5% solid content) and 0.05 parts by mass of wetting agent; first, the dispersant and pure water are stirred and blended in a planetary stirring device (with ultrasonic oscillation, vacuum, and high-speed dispersion functions) for 5 minutes at a time, the stirring rotation speed is 3100r / min, the revolution speed is 20r / min, and then the alumina powder is poured into a stirring tank for planetary stirring device (with ultrasonic oscillation, vacuum) , high-speed dispersing function) for secondary stirring and blending for 10 minutes to obtain a mixed solution, the stirring rotation speed of the equipment is 3100r / min, and the revolution speed is 20r / min; and ultrasound (frequency 50KHZ) is simultaneously performed during the above secondary stirring and blending process; after the secondary stirring, isopropanol, CMC, PMMA and wetting agent are added to the mixed solution, and the planetary stirring equipment is turned on again (the vacuum function is turned on, the rotation speed of the equipment is adjusted to 1000r / min, the revolution speed is 40r / min, and the ultrasonic oscillation frequency is 5kHz) for vacuum oscillation stirring and blending for 30 minutes to prepare a coating slurry.
[0039] Step 2, placing the PE film on a coating machine equipped with the coating slurry prepared in step 1 for single-side coating, controlling the coating speed to 30 m / min, and controlling the coating thickness after coating to 3 μm, to obtain a coating film;
[0040] Step 3, the coating film obtained in step 2 is pulled into a drying device through a traction roller for drying, the drying temperature is required to be 50° C., the drying time is 5 minutes, and a high cycle rate diaphragm is obtained.
[0041] Example 3
[0042] A method for preparing a high cycle rate diaphragm comprises the following steps:
[0043] Step 1, the required raw materials are 9 parts by mass of PMMA (35% solid content), 28 parts by mass of alumina, 55.8 parts by mass of pure water, 0.2 parts by mass of dispersant, 4 parts by mass of isopropanol, 2.96 parts by mass of CMC (5% solid content) and 0.04 parts by mass of wetting agent; first, the dispersant and pure water are stirred and blended in a planetary stirring device (with ultrasonic oscillation, vacuum, and high-speed dispersion functions) for 5 minutes at a time, and the stirring speed is 3100r / min and the revolution speed is 20r / min, and then the alumina powder is poured into a stirring tank for planetary stirring device (with ultrasonic oscillation, vacuum) The mixture was stirred and blended for 10 minutes in a planetary stirring device (with vacuum function and high-speed dispersing function) to obtain a mixed solution, wherein the stirring rotation speed of the device is 3100 r / min and the revolution speed is 20 r / min; and ultrasound (frequency 50 kHz) was simultaneously performed during the above-mentioned secondary stirring and blending process; after the secondary stirring, isopropanol, CMC, PMMA and a wetting agent were added to the mixed solution, and the planetary stirring device was turned on again (the vacuum function was turned on, the rotation speed of the device was adjusted to 1000 r / min, the revolution speed was 40 r / min, and the ultrasonic oscillation frequency was 5 kHz) for vacuum oscillation stirring and blending for 35 minutes to prepare a coating slurry.
[0044] Step 2, placing the PE film on a coating machine equipped with the coating slurry prepared in step 1 for single-sided coating, controlling the coating speed to 30 m / min, and controlling the coating thickness after coating to 4 μm, to obtain a coating film;
[0045] Step 3, the coating film obtained in step 2 is pulled into a drying device through a traction roller for drying, the drying temperature is required to be 50° C., the drying time is 5 minutes, and a high cycle rate diaphragm is obtained.
[0046] Comparative Example 1
[0047] A method for preparing a battery separator comprises the following steps:
[0048] Step 1, the required raw materials are 35 parts by mass of aluminum oxide, 55.8 parts by mass of pure water, 2 parts by mass of adhesive (isooctyl acrylate), 0.2 parts by mass of dispersant, 4 parts by mass of isopropanol, 3 parts by mass of CMC (5% solid content) and 0.05 parts by mass of wetting agent; first, the dispersant and pure water are stirred and blended in a planetary stirring device (with ultrasonic oscillation, vacuum, and high-speed dispersion functions) for 5 minutes at a time, the stirring rotation speed is 3100r / min, the revolution speed is 20r / min, and then the aluminum oxide powder is poured into the planetary stirring device (with ultrasonic oscillation, vacuum, and high-speed dispersion functions) ) for a second stirring and blending for 10 minutes to obtain a mixed solution, wherein the stirring speed of the equipment is 3100 r / min, and the revolution speed is 20 r / min; and ultrasound (frequency 50 kHz) is simultaneously performed during the above-mentioned secondary stirring and blending process; after the secondary stirring, isopropanol, CMC, adhesive (isooctyl acrylate), and wetting agent are added to the mixed solution, and the stirring equipment is turned on again (the vacuum function is turned on, the rotation speed of the equipment is adjusted to 1000 r / min, the revolution speed is 40 r / min, and the ultrasonic oscillation frequency is 5 kHz) and vacuum oscillation stirring and blending is carried out for 25 minutes to prepare a coating slurry.
[0049] Step 2, placing the PE film on a coating machine equipped with the coating slurry prepared in step 1 for single-sided coating, controlling the coating speed to 30 m / min, and controlling the coating thickness after coating to 2 μm to obtain a coating film.
[0050] Step 3, the coating film obtained in step 2 is pulled into a drying device through a traction roller for drying. The required drying temperature is 50° C. and the drying time is 5 minutes to obtain a primary coating film.
[0051] Step 4, taking the following raw materials by mass percentage: PVDF 10%, pure water 75%, dispersant 0.2%, isopropanol 6.6%, CMC (5% solid content) 8% and wetting agent 0.2%; firstly, the dispersant and pure water are stirred and blended in a planetary stirring device (with ultrasonic oscillation, vacuum, and high-speed dispersing functions) for 5 minutes at a stirring rotation speed of 3100 r / min and a revolution speed of 20 r / min, and then the PVDF powder is poured into the planetary stirring device (with ultrasonic oscillation, vacuum, and high-speed dispersing functions) for a second stirring and blending for 10 minutes. in, to obtain a mixed solution, the stirring rotation speed of the equipment is 3100r / min, and the revolution speed is 20r / min; and ultrasound (frequency 50KHZ) is simultaneously performed during the above-mentioned secondary stirring and blending process; after the secondary stirring, isopropanol, CMC, and wetting agent are added to the mixed solution, and the stirring equipment is turned on again (the vacuum function is turned on, the rotation speed of the equipment is adjusted to 1000r / min, the revolution speed is 40r / min, and the ultrasonic oscillation frequency is 5kHz) and vacuum oscillation stirring and blending is carried out for 30 minutes to prepare a coating slurry.
[0052] Step 5, placing the primary coating film obtained in step 3 on a coating machine equipped with the coating slurry prepared in step 4 for single-sided coating, controlling the coating speed to 30 m / min, and controlling the coating thickness after coating to 5 μm, to obtain a secondary coating film;
[0053] Step 6, the secondary coating film obtained in step 5 is pulled into a drying device through a pulling roller for drying, the drying temperature is required to be 50° C., and the drying time is 5 minutes, to obtain a battery separator.
[0054] The high cycle rate diaphragms obtained in Examples 1-3 and the diaphragm obtained in Comparative Example 1 are all white, and were tested. The results are shown in Table 1.
[0055] Table 1
[0056]
[0057] It can be seen from the above data that the use of PMMA coating can effectively improve the cycle rate of the battery during the charging and discharging process.
[0058] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.
Claims
1. A method for preparing a high cycle rate diaphragm, characterized in that: The following steps are involved: Step 1, first stirring and blending the dispersant and pure water, then adding alumina powder and stirring and blending for a second time to obtain a mixed solution, and simultaneously performing ultrasound during the above-mentioned second stirring and blending process, adding isopropanol, CMC, PMMA and a wetting agent to the mixed solution after the second stirring, stirring and blending by vacuum oscillation, and preparing a coating slurry; wherein the mass fraction ratio of PMMA, alumina, pure water, wetting agent, dispersant, isopropanol and CMC is (5-18): (20-30): (51.5-70.9): (0.03-0.09): (0.1-0.2): (3-6): (2.5-7); Step 2, coating the coating slurry obtained in step 1 on a PE film to obtain a coating film; Step 3, drying the coating film obtained in step 2 to obtain a high cycle rate diaphragm; In the step 3, the drying is performed by pulling the product into a drying device via a pulling roller.
2. The preparation method according to claim 1, characterized in that: In step 1, the dispersant is a silicate and the wetting agent is sodium hexametaphosphate.
3. The preparation method according to claim 1, characterized in that: In the step 1, the rotation speed of the stirring and blending is 2000-3100 r / min, the revolution speed is 20-40 r / min, and the stirring time is 5-45 min.
4. The preparation method according to claim 1, characterized in that: In the step 1, the rotation speed of the secondary stirring and blending is 2000-3100 r / min, the revolution speed is 20-50 r / min, and the stirring time is 10-30 min.
5. The preparation method according to claim 1, characterized in that: In the step 1, the ultrasound has an ultrasound frequency of 20-50KHZ.
6. The preparation method according to claim 1, characterized in that: In the step 1, the vacuum oscillation stirring and blending has a rotation speed of 1000-3000 r / min, a revolution speed of 20-40 r / min, an ultrasonic oscillation frequency of 5-60 kHz, and a stirring time of 15-30 min.
7. The preparation method according to claim 1, characterized in that: In the step 2, the coating is single-sided coating, the coating speed is 30-50 m / min, and the coating thickness is 2-4 μm.
8. The preparation method according to claim 1, characterized in that: In step 3, the drying temperature is 50-70° C., and the drying time is 1-5 min.
9. A high cycle rate diaphragm prepared by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Production process of coating diaphragm containing PMMA and copolymer of PMMA
CN106784533A